Collaborative Governance in Creating a Child-Friendly City in Banda Aceh City - Nurul Badria Ulfa; Paulus Israwan Setyoko (Universitas Teuku Umar, 2023)
Child-Friendly City is an effort to make cities safe, decent, and friendly for children. Child-Friendly Cities is a child-based development system integrated with government resources, the community, the media, community organizations, and the business world to guarantee children's rights. The City Government of Banda Aceh 2022 has again won an award as a Child-Friendly City in the Nindya category, and this category has increased at a level compared to last year. This achievement must be connected to the role and involvement of the government, the private sector, and the community. Therefore, this study aims to determine how far the Collaborative Governance process is in Creating a Child-Friendly City in Banda Aceh City. The research method used is a qualitative method with a type of research with a literature study approach obtained from books, journals, regulations, written sources, both printed and electronic, and others relevant to this research. After the data is collected, it will be analyzed following a research discussion raised using an interactive analysis model. The research findings are that the City of Banda Aceh can become a fully Child-Friendly City if it involves various parties or partners in making it happen. This is seen from three dimensions, namely (1) Principled Engagement; (2) Shared Motivation; (3) Capacity for Join Action, where collaboration between parties goes well.